Enhanced activity and stability of core-shell structured PtRuNix electrocatalysts for direct methanol fuel cells - Cheng, Yi; Shen, P.; Jiang, San Ping (2016)
© 2015 Hydrogen Energy Publications, LLC. Core-shell structured PtRuNix nanoparticles (NPs) with Ni-rich core and PtRu-rich shell are successfully synthesized on poly(ethyleneimine) functionalized carbon nanotubes (CNTs) through successively dealloying and annealing of PtRuNi alloy NPs. The best results are obtained after annealing the dealloyed PtRuNi NPs at 450 °C, forming a PtRu-rich shell and Ni-rich core structure with a surface composition of Pt:Ru:Ni = 1.0:1.13:0.24. PtRuNix shows significantly low onset potential and high activity for the methanol oxidation reaction (MOR), achieving a current density of 386.1 A g-1 Pt at 0.4 V vs Ag/AgCl. This is significantly higher than 101 A g-1 Pt measured on PtRuNi before dealloying and annealing treatment and 155 A g-1 Pt on the conversional Johnson Matthey PtRu/C electrocatalysts. At 0.4 V vs Ag/AgCl, the stable current for the MOR on PtRuNix electrocatalysts is 34.3 A g-1 Pt after polarization for 5000 s, which is significantly higher than 10.2 A g-1 Pt of PtRuNi and 9 A g-1 Pt of the conversional PtRu/C. The PtRuNix exhibits significantly improved microstructural stability under accelerated degradation test. The enhanced activity and stability is most likely related to the formation of intermetallic PtRu skinned shell and Ni rich core structures.